Transforming Primary Education in Sri Lanka : From a 'Subject' of Education to a 'Stage' of Education - Little, Angela; Aturupane, Harsha; Shojo, Mari (World Bank, Washington, DC, 2013)
Sri Lanka is a lower-middle income country with a per capita income of approximately US$ 2,400, and a population of around 20 million people. Sri Lanka's high rate of literacy is due to its sustained growth through the twentieth century. Primary education spans the first five grades of schooling, grades 1-5. Student's progress automatically to lower secondary education for four years of education in grades 6-9 and then on to upper secondary education in grades 10-11 for a two year course that culminates in the General Certificate of Education Ordinary level examination (GCE O-L). The curriculum for primary education is designed separately from those for subsequent stages of education. The primary education curriculum stage is encapsulated in a primary curriculum framework that derives from extensive debate during the 1990s in connection with the recommendations in 1997 of the national education commission, the work of the technical committee on primary education appointed by the presidential task force and detailed implementation work by the primary education unit of the national institute of education. Since 2003 the National Educational Research Centre (NEREC) based at the University of Colombo has administered tests in first Language, Mathematics and English to grade 4 children in a sample of schools country-wide. In the 2009 assessments a cut-off percentage of 80 percent rather than 50 percent were 48 percent in First Language, 53 percent in Mathematics and just 19 percent in English. The budget of the national Ministry of education includes a separate budget line for primary education but this money is allocated only to the primary sections of national schools. Province, zone, division and school budget do not separate allocations and expenditure for primary and secondary. There is no reason in principle why separate budget lines could not be created for most types of expenditure.